O08.4 Online Access to Home STI Specimen Collection and E-Prescriptions Linked to Public Health - is a Comparative Effectiveness Trial Feasible?. (13th July 2013) - Spielberg, F; Levy, V; Kapur, I; Lensing, S; Acevedo, N; Venkatasubramanian, L; Leivermann, C; Philip, S; Padian, N; Gaydos, C
Abstract : Background: Online STI testing and treatment may improve access at lower cost and with higher acceptability than clinic-based services. Methods: We conducted a demonstration (non-significant-risk medical device) study of an online system for STI education, vaginal specimen collection for chlamydia, gonorrhoea, and trichomonas testing, treatment, and partner notification, in collaboration with 4 San Francisco Bay area health departments. English and Spanish speaking women (18–30 yr) were recruited over 3 months through various methods. Results: The website had 6, 855 hits with a click through rate of 6.6%(450). Of 256 deemed eligible, 85%(217) enrolled. Among these, 54% (117) had not seen a clinician in the past year and 87%(142) had not had an STI test since last unprotected sex. Among those mailed a kit (213), 67% (143) returned the kit. Of these, 80% (115) of participants accessed test results online the same day results were posted, within 2 days (86%, 122) or by study end (92%, 131). STI prevalence was 5.6% (chlamydia and trichomonas). All STI infected participants received treatment either the same day (75%, 6/8) at a pharmacy or within 7 days at a clinic (25%, 2/8). Internet recruitment reached the highest number of participants (100/217, 46%), while advertising on subways reached the highest number of positives (5/8, 63%). Of 106 participants completing follow-up surveys, 98% (104) indicated the site was easy to use and 98% (104) would recommend the project to a friend. No negative outcomes were reported. If participating in a future trial, 94% (100) would prefer an online system over clinic-based care. Conclusions: An online system for STI testing and treatment appears feasible, and highly acceptable to participants. We recommend a future comparative effectiveness trial to determine whether an online system can increase testing and treatment of STI infections at lower cost and with higher acceptability than clinic-based care.